CREDIT RISK IN ISLAMIC BANKING: AN IN-DEPTH ANALYSIS OF CREDIT RISK MANAGEMENT AND RISK-SHARING MECHANISMS IN INDONESIAN ISLAMIC FINANCIAL INSTITUTIONS - Alfiana Alfiana; Sulistyo Budi Utomo; Muhammad Syafri; Al-Amin; Azmi Syarif (ADISAM Publisher, 2023)
This research extensively examines credit risk management within the unique realm of Islamic banking institutions operating in Indonesia. Islamic finance, guided by principles of ethical finance and profit-and-loss sharing (PLS) contracts, introduces distinctive complexities into the credit risk domain. The primary objective is to scrutinize the intricacies of credit risk management in Islamic banking, particularly in the Indonesian context, a significant hub for Islamic finance. The study dissects several complex dimensions: It delves into the profound intricacies of risk-sharing mechanisms inherent in Islamic finance. The research explores how profit-and-loss sharing contracts, like Mudarabah and Musharakah, reshape credit risk dynamics and the distribution of risk between financial institutions and clients. Additionally, the research investigates the unique collateralization methods in Islamic banking, compliant with Sharia principles, and their impact on credit risk and recovery processes following default. A detailed analysis of diverse contractual structures used in Islamic finance, including Ijarah and Murabahah, assesses their influence on credit risk profiles and risk mitigation strategies. Moreover, the study examines the regulatory framework governing Islamic finance in Indonesia, considering how regulators harmonize Islamic financial principles with the imperative of maintaining financial stability. The complexities of default management and recovery procedures in Islamic finance are also explored, encompassing debt restructuring, arbitration, and Sharia-compliant debt recovery mechanisms. This research combines quantitative analysis and qualitative investigation to understand Indonesian Islamic banking comprehensively. The findings offer valuable insights into the intricate landscape of credit risk within Islamic finance, with broader implications for the global industry.